PERUBAHAN UNDANG-UNDANG PAJAK PENGHASILAN DAN PERANNYA DALAM MEMPERKUAT FUNGSI BUDGETAIR PERPAJAKAN - Venti Eka Satya; Galuh Prila Dewi (Jurnal Ekonomi & Kebijakan Publik, 2010)
The income tax law that was passed in Indonesia in 1983, has been amended for several times. This study discusses about the objectives and main points of changes have been made to income tax laws. This paper also discusses the impact of the changes in general and whether changes in tax rates have a significant impact on the state income tax revenue. The portion of tax revenue derived from income tax showed an increase as well as the increasing number of taxpayers. It is one positive side of the reform legislation of this income, but the changes did not have a significant influence to the state revenues. This is caused by the motif of that changes is not only to meet the budgetair function, but also for the other tax functions.